Pengaruh Keselamatan Dan Kesehatan Kerja Terhadap Produktivitas Kerja Karyawan (Studi Pada Pt. Duta Beton Mandiri) - Muhamad Adis Prayoga; Abd Kodir Djaelani; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis research was conducted to find out how much influence the Occupational Safety and Health variables on Employee Productivity. Study at PT. Duta Beton Mandiri Pasuruan. In this study the population of 44 people using saturated sampling. The method of sampling is, employees who work at PT. Duta Beton Mandiri Pasuruan. To find out the data that will be examined later, this study uses a way to distribute questionnaires to better know the opinions of employees by filling out the statements that have been attached to the questionnaire. Also in this study using SPSS measuring tools to test data in the form of instrument testing, multiple linear regression analysis, testing classic assumptions, and testing hypotheses. From this study produced several conclusions that mention that the Occupational Safety and Health variables influence together so that it can increase the work productivity of employees of PT. Duta Beton Mandiri Pasuruan. While partial work safety does not affect employee work productivity, while occupational health has an influence on employee work productivity.Keywords: Occupational Safety and Health